A Study on Effectiveness of FR4 as a Dielectric Material for Radial Line Slot Array Antenna for Wireless Backhaul Application - Imran , Mohd Ibrahim; Tharek, Abdul Rahman (2011)
The Radial Line Slot Array (RLSA) Antenna is known for its good characteristics such as low profile, low cost, aesthetically pleasing, ease of installation and simple structure. RLSA antenna normally developed using polypropylene as a dielectric structure in the middle of radiating plate and ground plate. This research is focus on applying FR4 as a dielectric plate. The prototypes has been simulated, fabricated and the measured. The measurement obtained a -15dB of return loss, 11.5dBi of directivity gain and 5% antenna bandwidth.